Comprehensive profiling of circRNAs reveals stimulus-specific networks and core regulators of cellular senescence - Mingxia Ge; Zimo Liu; Xiaoxiao Zhao; Xiaodong Zhan; Shan Jiang (PLoS ONE, 2026)
Cellular senescence, a hallmark of aging and age-related disorders, is characterized by irreversible cell cycle arrest and profound molecular alterations. Although previous transcriptomic studies have largely focused on protein-coding genes, the expression landscape of circular RNAs (circRNAs) during senescence remains poorly defined. Here, we systematically profiled circRNA expression across multiple senescence models using two human fibroblast lines (WI38 and IMR90) subjected to four distinct senescence-inducing stimuli: replicative senescence (RS), oncogene-induced senescence (OIS), doxorubicin-induced senescence (DOX), and ionizing radiation (IR). Through rigorous analysis, we identified 39,187 high-confidence circRNAs, classifying them into stimulus-specific (SS-circRNAs) and general senescence-associated circRNAs (GS-circRNAs). Among them, 24 GS-circRNAs exhibited conserved expression trends across different senescence models, and eight core circRNAs displayed consistent expression changes in both fibroblast lines, suggesting their potential as universal senescence biomarkers. Functional enrichment and co-expression network analyses revealed that SS-circRNAs participated in pathway-specific processes such as ribosome biogenesis, mitochondrial regulation, ubiquitin-mediated signaling, and RNA metabolism. Collectively, our findings provide a comprehensive atlas of circRNA dynamics across diverse senescence programs and identify candidate circRNAs that may serve as novel diagnostic or therapeutic targets for age-related diseases.